From unlikely pairings to functional nanocomposites: FeTi–Cu as a model system - Lukas Schweiger; Daniel Kiener; Michael Burtscher; Erhard Schafler; Gregor Mori; Florian Spieckermann; Jürgen Eckert (Materials Today Advances, 2023)
In order to develop materials for energy storage, a bulk nanocomposite with a composition of FeTi-25 vol% Cu was prepared by high-pressure torsion, with FeTi as functional phase for hydrogen storage and Cu as ductile phase to improve the processability. Despite the use of such a highly ductile auxiliary phase, the processability remained challenging due to strain localization in the softer Cu. This behavior is most pronounced at room temperature, and no nanocomposites were formed. At elevated temperatures, the strong strain rate sensitivity of the flow stress of the nanocrystalline Cu facilitates the formation of a FeTi–Cu nanocomposite due to a self-reinforcing process. Nevertheless, fragmentation of FeTi is limited because the resulting massive strain hardening prevents controlled processing at temperatures <250 °C, and Cu-rich shear bands develop at temperatures >250 °C. Satisfactory microstructural homogeneity is only achieved at the highest deformation temperatures of 550 °C. Overall, this study highlights that for unlikely material pairings, as often required in the pursuit of superior functional materials, the mechanical behavior of the phases involved and their interplay remains critical and must be thoroughly investigated when aiming for controlled structural homogeneity of bulk nanomaterials.